Cosmic Tango Between the Very Small and the Very Large: Addressing CMB Anomalies Through Loop Quantum Cosmology - Ashtekar, Abhay; Gupt, Brajesh; Sreenath, V. (Frontiers in Astronomy and Space Sciences, 2021)
While the standard, six-parameter, spatially flat Lambda-CDM model has been highly successful, certain anomalies in the cosmic microwave background bring out a tension between this model and observations. The statistical significance of any one anomaly is small. However, taken together, the presence of two or more of them imply that according to standard inflationary theories we live in quite an exceptional universe. We revisit the analysis of the PLANCK collaboration using loop quantum cosmology, where an unforeseen interplay between the ultraviolet and the infrared makes the primordial power spectrum scale dependent at very small k. Consequently, we are led to a somewhat different Lambda-CDM universe in which anomalies associated with large scale power suppression and the lensing amplitude are both alleviated. The analysis also leads to new predictions for future observations. This article is addressed both to cosmology and LQG communities, and we have attempted to make it self-contained.